2016
DOI: 10.1038/nature18952
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine protection against Zika virus from Brazil

Abstract: Zika virus (ZIKV) is a flavivirus that is responsible for an unprecedented current epidemic in Brazil and the Americas1,2. ZIKV has been causally associated with fetal microcephaly, intrauterine growth restriction, and other birth defects in both humans3–8 and mice9–11. The rapid development of a safe and effective ZIKV vaccine is a global health priority1,2, but very little is currently known about ZIKV immunology and mechanisms of immune protection. Here we show that a single immunization of a plasmid DNA va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
562
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 482 publications
(597 citation statements)
references
References 32 publications
22
562
1
8
Order By: Relevance
“…In the viremia model [39,40], temoporfin treatment resulted in about 100-fold reduction in ZIKV-induced viremia in immunocompetent Balb/C mice compared to the vehicle control ( Figure 5A). In the lethal A129 mouse model [41,42], all the ZIKV-infected animals treated with vehicle died with typical neurological symptoms including hind limb weakness and paralysis.…”
Section: In Vivo Protection Of Mice From Lethal Challenge Of Zikvmentioning
confidence: 99%
“…In the viremia model [39,40], temoporfin treatment resulted in about 100-fold reduction in ZIKV-induced viremia in immunocompetent Balb/C mice compared to the vehicle control ( Figure 5A). In the lethal A129 mouse model [41,42], all the ZIKV-infected animals treated with vehicle died with typical neurological symptoms including hind limb weakness and paralysis.…”
Section: In Vivo Protection Of Mice From Lethal Challenge Of Zikvmentioning
confidence: 99%
“…However, the sudden ZIKV outbreak in South America alerted health authorities and the public to develop a vaccine. Preclinical studies have demonstrated a protective role of CD8 T cells and antibodies against ZIKV infection, the latter being sufficient for complete protection [67][68][69][70]. However, cocirculation of DENV, WNV and ZIKV has been reported in several countries and previous studies suggested an immunological cross-reactivity between viruses, which may drive immune-mediated enhancement [71][72][73].…”
Section: Zika Virusmentioning
confidence: 96%
“…Preclinical studies demonstrated that both vaccines induced high neutralising antibody titers and completely protected animals against ZIKV challenges [67,68,75].…”
Section: Inactivatedmentioning
confidence: 99%
See 2 more Smart Citations